An integrated model of e-learning continuance intention in Indonesia. (7th May 2019) - Ramadiani, Ramadiani; Azainil, Azainil; Frisca, Frisca; Hidayanto, Achmad Nizar; Herkules, Herkules
There had been some research concerning behaviour in using e-learning system. Most of the analysis focuses on the students' behavioural intention to use the system, without doing further analysis to find out their continuance intention to use it again. Therefore, this research aims to develop a model that describes the influencing factors on e-learning continuance intention of Indonesian students. Analysis in this research is focused on the investigations of the e-learning satisfaction, e-learning usefulness, and e-learning effectiveness, from the four main aspects: e-learning materials/multimedia, service quality, interaction, and learner's characteristics. By using structural equation modelling approach, several analyses were conducted to 635 respondents' data, obtained from various universities in Indonesia. This research found that almost all of the factors analysed in this research have a significant influence on continuance intention of Indonesian students, with e-learning satisfaction and e-learning usefulness as the main factors that influence directly, and navigation, reliability, tangibles, self-efficacy, and learner-content interaction as the main factors that influence indirectly.